National identity as one of the aspects of personal identity - Antinienė, Dalia (Psichologija, 1999)
In the whole complex of personal identities a new sphere has been singled out recently i. e. – national identity. This research has been devoted to collect as many empirical facts on this issue as possible and to try, on the grounds of Marcia’s conception, to determine the statuses of identity and the factors influencing it and to pick out the main dimensions of national identity. A research has been made to compare the peculiarities of young people whose parents are of the same nationality and of those from mixed families. Achieved results show the importance of national identity to a person and the way it combines with other aspects of identity. Different statuses of national identity which are determined by such environmental factors as homogeneous or heterogeneous family in national aspect, the living place, the language etc. were revealed together with the combinations of these factors.